2014
DOI: 10.1155/2014/298795
|View full text |Cite
|
Sign up to set email alerts
|

High Nuclear Expression of HDGF Correlates with Disease Progression and Poor Prognosis in Human Endometrial Carcinoma

Abstract: Aims. This study examined the correlation between high nuclear expression of hepatoma-derived growth factor (HDGF) and clinicopathologic data in endometrial carcinoma (EC), including patient survival. Methods. One hundred and twenty-two endometrial carcinoma (EC) patients from 2002 to 2008 were reviewed in the study. HDGF expression in tumor tissues was examined using immunohistochemistry (IHC), and its association with clinicopathological parameters was evaluated. Tumors with 80% or more nuclei staining were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…HDGF� which is located on chromosome 1 at the q21-q23 region, is overexpressed in different types of cancer, including colorectal cancer (36), hepatocellular carcinoma (37), cervical cancer (38) and ovarian cancer (39). HDGF is also highly expressed in EC (21). A high HDGF expression is positively associated with FIGO stage (21).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…HDGF� which is located on chromosome 1 at the q21-q23 region, is overexpressed in different types of cancer, including colorectal cancer (36), hepatocellular carcinoma (37), cervical cancer (38) and ovarian cancer (39). HDGF is also highly expressed in EC (21). A high HDGF expression is positively associated with FIGO stage (21).…”
Section: Discussionmentioning
confidence: 93%
“…HDGF is also highly expressed in EC (21). A high HDGF expression is positively associated with FIGO stage (21). Patients with EC and a high HDGF expression exhibit lower overall survival rates when compared with patients exhibiting a low HDGF expression (21).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The following articles were also excluded: three duplicated publications (Zhou et al, 2007b;Zhou et al, 2010a;Yang et al, 2014); three without data for HR and 95%CI calculations and adequate contact with the investigators could not be established (Natrajan et al, 2006;Mao et al, 2008;Hanada et al, 2013); two with a sample size<50 (Hsu et al, 2012;Tao et al, 2014); two in which HDGF expression was not detected by IHC methods (Savola et al, 2009;Zhang et al, 2010); three uncorrelated. Finally, 26 cohort studies were found eligible for the meta-analysis (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Lin et al, 2012;Han et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Zhang et al, 2014), containing 32 datasets (29 datasets for OS; 17 datasets for DFS) were qualified to the standard of the meta-analysis. The main characteristics of the selected studies were summari...…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…In recent years, elevated levels of hepatoma-derived growth factor (HDGF) have been observed in a variety of malignancies and high levels of HDGF appears to be associated with increased malignancy across cancers, as witnessed by the correlation with adverse characteristics such as poor patient survival (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Savola et al, 2009;Zhang et al, 2010;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Ye et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Hsu et al, 2012;Lin et al, 2012;Han et al, 2013;Hanada et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Yang et al, 2014;Zhang et al, 2014). As a multifunctional protein Bao et al, 2014) widely expressed by many types of human cells, HDGF is involved in the regulations of a myriad of cancer cell activities during cancer transformation (Yang et al, 2013), apoptosis , angiogenesis (Ren et al, 2009), and metastasis (Chen et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%